Tax Accounting and Livestock in Australia Insights from the Wade Case - Fullarton, Lex; Pinto, Dale (ibidem Press, 2024)
The authors take an in-depth look at an accepted practice of classifying ALL animals held in a business of primary product in Australia as revenue assets regardless of the function they perform in that business. This practice denies retiring farmers tax concessions granted to other businesses. They describe the practice as unfair, and after a deep examination of the circumstances that gave rise to the generally accepted accounting and tax interpretation, they find that it is not true.